FEATURES OF SURFAGON ACTION DURING DIFFERENT ROUTES OF ITS ADMINISTRATION - Abror Azamovich Kholikov (Scholar Express Journal, 2024)
This scientific article describes the results of experiments conducted on mice to determine the strength and effectiveness of administering the surfagon drug using different routes of administration. In particular, it acts most strongly when administered intramuscularly and subcutaneously (increase in the weight of the uterus and ovaries by 8.36 and 8.31, respectively times), then through the mouth (weight increase by 4.94 times) and even weaker with intravaginal administration (weight increase by 4.29 times).
Keywords: Surfagon; injection; hormones